Effective NETWORKING FOR BUMIPUTERA ENTREPRENEURS - Siti Sarah Omar (2020)
The overall aim of the book is to explore the dynamics of strong and weak ties within entrepreneurial networks during periods when the entrepreneurs face tipping points, and to show how network interactions can affect the subsequent performance of small businesses. Many studies have explored the mix of strong and weak ties in small businesses, linking them to stages of business development. More recent scholars, however, has conceptualised firm growth through the notion of tipping points that must be successfully tackled in order to continue along the development path. While the importance of network ties has been well documented in relation to growth stages, only limited work has been done to investigate the contribution that strong and weak ties make as a firm faces specific tipping points. This book therefore aims to provide an extensive understanding of the readers in two aspects that are: (1) The configuration of network ties in the entrepreneurial ventures of Malaysian Bumiputera (Indigenous) SME entrepreneurs; (2) The change and development of network ties in relation to the tipping points faced by these entrepreneurs.This book uncovers six themes when characterising the configurations of entrepreneurial network ties: personal network, business network, professional network, reputaion network, competition network and community network. In addition, the discovery of the existence of a dormant tie associated with the reputation network has provided support for the argument centered on the multiplicity of entrepreneurial network ties in small businesses. Human capital and attitudes are significant for entrepreneurs when deciding the strength of their relationships. Network changes occur not only due to staged life cycle processes of business, but due to also when entrepreneurs face tipping points.